2010
DOI: 10.1002/chir.20870
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism eigenspectra of polyproline II and β‐strand conformers of trialanine in water: Singular value decomposition analysis

Abstract: Despite that a number of experimental and theoretical investigations have been carried out to determine the structure of trialanine in water, the reported populations of polyproline II (PPII) and β-strand conformers vary and were found to be dependent on which spectroscopic method was used. Such discrepancies are due to limitations of different spectroscopic methods used. Here, the temperature- and pH-dependent circular dichroism (CD) and NMR experiments have been carried out to develop a self-consistent singu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 71 publications
8
63
0
Order By: Relevance
“…Cho and co-workers showed that the average ppII population over two peptide bonds in (Ala) 3 changes from 88% to 65% by simply changing the reference structure ensembles from Gromos 43A1 to AMBER ff03 but using the same experimental J -coupling constants and Karplus equations. 31 Such dependence on force fields demonstrates the need for accurate MD simulations and validation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho and co-workers showed that the average ppII population over two peptide bonds in (Ala) 3 changes from 88% to 65% by simply changing the reference structure ensembles from Gromos 43A1 to AMBER ff03 but using the same experimental J -coupling constants and Karplus equations. 31 Such dependence on force fields demonstrates the need for accurate MD simulations and validation.…”
Section: Resultsmentioning
confidence: 99%
“…30 Cho and coworkers developed a self-consistent singular value decomposition based method to fit CD spectra and NMR J-coupling constant simultaneously, and determined the ppII population of the central residue in (Ala) 3 is 66%. 31 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fact that the 3 J HNa coupling constants of the dipeptides are distributed in the range from 5.5 to 9.6 Hz indicates that the backbone conformations of dipeptides are mixtures of PP II and b-strand structures consistent with the experimental finding by Avbelj et al (2006) who showed that the fractional populations of PP II and b-strand conformations are dominant in 19 blocked amino-acids (N-acetyl-X-N 0 -methylamide) except for Gly. In our previous work, we also showed that the CD spectra of the blocked dipeptides can be described as a linear combination of the CD eigenspectra of the PP II and bstrand conformations (Oh et al 2010(Oh et al , 2012 and further examined the validity of a two-state approximation by comparing our results with previous works done by other groups (Hagarman et al , 2011. However, it should also be emphasized that the fitting analysis method using reference values of two representative conformations such as PP II and b-strand is intrinsically approximate in nature.…”
Section: Resultsmentioning
confidence: 96%
“…However, over the last decade, it has been shown that the backbone conformations of such oligopeptides are not random but adopt PP II , b-strand, and some turn structures that are in dynamic equilibria. (Avbelj et al 2004(Avbelj et al , 2006Cho et al 2010;Pappu and Rose 2002;Schweitzer-Stenner et al 2002Schweitzer-Stenner and Measey 2007;Shi et al 2002a, b) Thus, the notion that the conformation of small peptide in aqueous solution is a random coil has been proven to be incorrect. Although the scalar coupling constants of short peptides have been widely used to quantitatively determine the backbone conformational distribution, the NMR chemical shifts of short peptide H N and H a have not been fully explored to elucidate the relationship between the backbone conformational distribution of unfolded proteins and that of short peptides.…”
Section: Chemical Shifts Of Peptide H N and H Amentioning
confidence: 95%
See 1 more Smart Citation